Tari Tradisi Gorontalo Tidi Lo O’ayabu Dalam Persprektif Humanisme - Djafar, Nurlia (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
The traditional dance Tidi Lo O’ayabu is one of Gorontalo’s cultural heritages, rich in social, spiritual, and aesthetic values. This study aims to examine Tidi Lo O’ayabu from a humanistic perspective, focusing on how the dance represents respect for human dignity, social solidarity, and the harmony of life. The research employed a qualitative approach through literature review, performance observation, and interviews with Gorontalo artists and cultural figures. The findings reveal that Tidi Lo O’ayabu is not merely an artistic expression of movement but also a manifestation of humanistic values that emphasize togetherness, respect for women, and a harmonious relationship between humans and their environment. The dance functions as an educational and cultural medium that strengthens Gorontalo’s identity while demonstrating the relevance of traditional arts in addressing modern humanitarian challenges. Thus, Tidi Lo O’ayabu can be understood as a living practice of humanism within local culture.